Plasticizer effect and comparative evaluation of cellulose acetate and ethylcellulose-HPMC combination coatings as semipermeable membranes for oral osmotic pumps of naproxen sodium - Ramakrishna N.; Mishra B. (My University, 2025)
The objective of this study was to compare the performance of cellulose acetate (CA) and ethylcellulose (EC)-HPMC combination coatings as semipermeable membranes (SPMs) for osmotic pump tablets (OPTs) of naproxen sodium (NPS) so as to deliver a constant, predetermined amount of drug in solution form over a fixed span of time, independent of external environmental conditions. Osmotic pump tablets were designed with different coating variables and optimized in terms of nature of plasticizer, membrane thickness, and orifice diameter. The effect of insertion of an inner microporous film around the NPS core to minimize deformation of the SPM due to peristaltic movement of the gut was also studied. Osmotic pump tablets composed of membranes with water-soluble plasticizer, propyleneglycol (PG), released drug mainly through diffusion, whereas those designed with CA and EC-HPMC (4:1) coats containing water-insoluble plasticizer, castor oil, released their contents by perfect zero-order kinetics over a prolonged period of time, though the average release rate that could be achieved with the EC-HPMC (4:1) membrane was only about half the rate achieved with the CA membrane for the same membrane thickness. Release rates for both the membranes decreased with increasing membrane thickness and were found to be independent of orifice diameter, agitation intensity, and pH of the dissolution medium.